Assessing appropriateness of osteoarthritis care using quality indicators: a systematic review. Issue 5 (17th June 2015) - Basedow, Martin; Esterman, Adrian
Abstract Rationale, aims and objectives Quality indicators (QIs) derived from the review of medical records, administrative databases, and patient questionnaires and interviews have been frequently used to assess the quality of osteoarthritis (OA) care. The purpose of this review is to summarize studies that have assessed the quality of OA care using QIs. Method We systematically searched MEDLINE, EMBASE, CINAHL and PsycINFO for English‐language studies indexed by October 2014. Articles were included if they used any QIs for assessing the quality of OA care. We summarized the results of these studies, and with meta‐analysis, generated an overall conclusion about the quality of care as measured by QIs for each treatment domain for OA care. Results Fourteen studies assessed as being of high‐quality were included in the review, with the number of QIs ranging from 1 to 21. Four of the 14 studies solely assessed the quality of OA care, while the other studies assessed health care quality for a range of conditions that included OA. The quality of OA care as assessed by a meta‐analysis of QI pass rates across studies was suboptimal for all treatment domains (pass rates: pain and functional status assessment – 48.5%, 95% CI 32.6–64.6%; non‐drug treatment – 36.1%, 95% CI 27.8–44.7%; drug treatment – 37.5%, 95% CI 30.8–44.5%; surgical referral – 78.9%, 95% CI 57.4–94.2%). Conclusion Despite efforts made at improving care for patients with OA, the wide divergence between evidence and consensus‐based recommended care and practice has been reaffirmed.